Advancing responsible management education (RME) and education for sustainable development (ESD) through online resources - Librizzi, F.; Parkes, C.; Simaens, A. (The future of responsible management education: University leadership and the digital transformation challenge, 2023)
Business and management related education, as well as higher education more broadly, is called upon to play a very important role in integrating responsibility as well as sustainability across their teaching and learning. As we have now entered the Decade of Action for the 2030 Agenda and the Sustainable Development Goals (SDGs), this need becomes even more critical and it is suggested that “advancements we see in the field (of responsible business and management education) could be in part due to a greater understanding of the nature of the subject with all its complexity and challenges” (Moosmayer, D. C., Laasch, O., Parkes, C., & Brown, K. G. The SAGE handbook of responsible management learning and education. SAGE. https://play.google.com/store/books/details?id=31jGDwAAQBAJ, 2020, p.24). While the COVID-19 pandemic has shaken up traditional ways of teaching and learning, the role that online content and tools, particularly, Open Educational Resources (OER) can have (in advancing responsible management education (RME) and sustainable development) in remote teaching and learning has also been made more evident. This chapter aims to provide a better understanding on how online resources and specifically content and tools, including Massive Open Online Courses (MOOCs) and Open Educational Resources (OER) can be utilized to enhance RME and discuss some of the challenges including the role of the COVID-19 pandemic. The chapter will feature the case of the SDG Academy—the flagship education initiative of the Sustainable Development Solutions Network (SDSN), a global initiative for the United Nations—with the mandate of creating and curating the best available educational content on sustainable development and making it available as a global public good (https://sdgacademy.org/). With a large catalogue of MOOCs, videos and podcasts this initiative aims to support the current and next generation of educators, practitioners and citizens to advance sustainable development everywhere. Finally, the chapter will discuss the opportunities and challenges and provide recommendations for faculty and practitioners on how to make the most of online content and tools to teach and learn responsibility and sustainable development.